Effects of proprioceptive training on sports performance: a systematic review - Yilmaz, O.; Soylu, Y.; Erkmen, N.; Kaplan, T.; Batalik, L. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Proprioception, the ability to sense the body`s position and movement, is essential for athletic performance and physical well-being. The literature highlights the importance of proprioceptive training in rehabilitation, sports performance, injury prevention, and motor function enhancement. Targeted training programs can improve balance, coordination, motor learning, and overall physical performance. This systematic review aimed to examine the effects of proprioceptive training methods on sports and athletic performance.